ANALISIS TINGKAT KEPUASAN KERJA KARYAWAN PADA YAYASAN ABC - Siti Nur Rohmah; Tri Andriani; Amalia, Nurulita; Ilham, Ilham; Mia Rahma Dewi (JURNAL LENTERA BISNIS, 2026)
Job satisfaction is one of the important aspects in human resource management because it directly affects employee productivity, loyalty, and performance. Employees with high job satisfaction tend to show good work motivation, minimal conflicts, and are able to contribute optimally to achieving organizational goals. In the context of educational institutions, job satisfaction becomes a crucial factor because it is directly related to the quality of educational services and the teaching-learning process. ABC Foundation, as an educational institution, has a strategic role in shaping a quality generation, but is faced with the phenomenon of job dissatisfaction experienced by some teachers and staff. The issues include aspects of welfare, workload, and the internal communication system, which are considered not yet optimal, resulting in decreased motivation, increased complaints, and fluctuations in employee performance. This study aims to analyze the level of job satisfaction among employees at ABC Foundation and to identify the main factors affecting it. The results of this study are expected to provide a clear picture of the employees' job satisfaction situation and serve as a basis for the foundation in formulating more effective human resource management policies to improve employee performance and the quality of educational services sustainably.